Hydrochemical Characteristics and Evolution Mode of Cold Seeps in the Qiongdongnan Basin, South China Sea - Zhifeng Wan; Chongmin Chen; Jinqiang Liang; Wei Zhang; Wei Huang; Pibo Su (Geofluids)
Submarine cold seeps have recently attracted significant attention and are among the most effective indicators of gas hydrate in the oceans. In this study, remotely operated vehicle (ROV) observations, seismic profiles, core sediments, bottom seawater, and fluid vented from cold seeps in the deep-water Qiongdongnan Basin were used to investigate the origin and evolution of cold seeps and their relationships with gas hydrate. At stations A, B, and C, inactive cold seeps with dead clams, cold seep leakage with live clams, and active cold seeps with a rich mussel presence, respectively, were observed. The salinity and Na+ and Cl- concentrations of the cold seeps were different from those of typical seawater owing to gas hydrate formation and decomposition and fluid originating from various depths. The main ion concentrations of the bottom seawater at stations B and C were higher than those at station A, indicating the substantial effects of low-salinity cold seep fluids from gas hydrate decomposition. The Na+-Cl-, K+-Cl-, Mg2+-Cl-, and Ca2+-Cl- diagrams and rare earth element distribution curves of the water samples were strongly affected by seawater. The concentrations of trace elements and their ratios to Cl- in the bottom seawater were high at the stations with cold seeps, suggesting the mixing of other fluids rich in those elements. Biochemical reactions may also have caused the chemical anomalies. Samples of HM-ROV-1 indicated a greater effect of upward cold seep fluids with higher B/Cl-, Sr/Cl-, and Ba/Cl- values. Moreover, the Re/Cl- value varied between fluid vents, possibly due to differences in Re precipitation strength. Differences in cold seep intensity are also believed to occur between areas. The cold seep fluxes changed from large to small before finally disappearing, showing a close connection with gas hydrate formation and decomposition, and influenced the local topography and ecosystems.